2008
DOI: 10.3382/japr.2008-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Litter Amendments on Ammonia Volatilization and Nitrogen Content of Poultry Litter

Abstract: Ammonia volatilization from poultry manure contributes to atmospheric N pollution, negatively affects poultry performance, and decreases the fertilizer value of manure. The objective of this study was to evaluate the effects of alum [Al 2 (SO 4 ) 3 ·14H 2 O], liquid alum, high acid alum (A7), aluminum chloride (AlCl 3 ·6H 2 O), fly ash, Poultry Litter Treatment (PLT), and Poultry Guard (PG) litter amendments on NH 3 volatilization and N contents in litter. Two laboratory studies were conducted for 42 d each. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 29 publications
5
41
2
Order By: Relevance
“…As a result, alum is commonly used as a litter additive that can suppress the production of NH 3 and is available in both a dry and liquid form. Previous studies have shown that adding alum or liquid alum to poultry litter reduced NH 3 emissions by over 75% under commercial and laboratory conditions (Choi and Moore, 2008a;Moore et al, 2000). In addition, the reduced atmospheric ammonia resulted in improved poultry production and produced benefits to cost-effective best management practices (Moore et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, alum is commonly used as a litter additive that can suppress the production of NH 3 and is available in both a dry and liquid form. Previous studies have shown that adding alum or liquid alum to poultry litter reduced NH 3 emissions by over 75% under commercial and laboratory conditions (Choi and Moore, 2008a;Moore et al, 2000). In addition, the reduced atmospheric ammonia resulted in improved poultry production and produced benefits to cost-effective best management practices (Moore et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Choi and Moore [31] also reported that ammonia nitrogen was about 1.3-2.3 g/kg in control litter and was about 1.0-7.1 g/kg in the litters with various amendments. One of the most important factors that can affect ammonia volatilization is litter pH [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Choi and Moore [31] also reported that ammonia nitrogen was about 1.3-2.3 g/kg in control litter and was about 1.0-7.1 g/kg in the litters with various amendments. One of the most important factors that can affect ammonia volatilization is litter pH [31] . Reece et al [32] suggested that very little ammonia was released from litter having pH below 7, whereas more ammonia was rapidly released from litter having pH above 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But these conversions (solid urea dissolution and urea hydrolysis) need to be finished prior to ammonia emission 77 . Higher pH levels (above 7.0) which can be observed with YSE inclusion 52 , is favorable for ammonia release since ammonia is a major form of gas emitted under this condition [78][79][80] . Factors such as different collection time correspond with varying degrees of manure moisture 52 , which need to be noticed to minimize the inaccuracy of experiment as well.…”
Section: Gas Mitigation Mechanisms Of Monogastric Animalsmentioning
confidence: 99%